Identification of Hazards and Assessment of Risks associated with the Harvesting of Coffee - Palomino-García, Lady R.; Vargas-Vásquez, Martha L. (Puerto Rico Health Sciences Journal, 2023)
Objective: To study the factors associated with the occupational risks affecting coffee harvesters from Timbío, Cauca, Colombia. Methods: This descriptive study assessed workplace conditions, aiming to design a mitigation proposal that would help alleviate the dangers currently facing the studied population. The data were collected through 19 visits to the coffee plantations. A survey to characterize workers and determine the presence of musculoskeletal lesions was applied; in addition, the Colombian Technical Guide (GTC 45, by its initials in Spanish) was consulted. Results: Coffee harvesting comes with several high priority risks, of which those that are biomechanical stand out. These are the result of strained positions, antigravity postures, repetitive movements, high physical effort, and the manual handling of heavy objects. Additionally, there are psychosocial risks attend the kind of contract, the low wages, the lack of social security, and the lack of affiliation with the occupational risk-management system. During the data collection, 18% of the workers reported having had an occupational accident while harvesting coffee. Conclusion: The process for identifying danger and assessing risk established, for all the cases, a level 1 risk. According to the rating scale of the GTC 45, such a level is unacceptable. We concluded that it is necessary to take immediate measures to control the identified dangers. To improve the health of the members of the studied sample, we propose the implementation of an epidemiological surveillance system for musculoskeletal injuries.